Issues of Compliance of Financial Statements with International Standards - Egamberdiyeva Salima Rayimovna; Aralov Sabir Javli ugli (HM Journals, 2022)
This article discusses the methodological foundations, stages and main directions of the process of adapting financial reporting in the economy of Uzbekistan to international standards. The international experience in this area was studied and the necessary proposals and recommendations were made